PENGARUH MEDIA PEMBELAJARAN BERBASIS ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) TERHADAP MINAT BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS DI SDN 156 MAGA LOMBANG - Putri Meida Sari; Eka Yusnaldi; Andina Halimsyah Rambe (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The research that has been carried out is entitled "The Influence of ICT (Information and Communication Technology) Based Learning Media on Students' Interest in Learning in Class IV Science and Science Subjects at SDN 156 Maga Lombang", based on the problem that arises in science and science learning, namely the lack of interest in students' learning due to the method used. used by teachers is still less varied or also called conventional methods. The research used a quantitative approach, namely experimental research. The research population was all 4th grade students at SDN 156 Maga Lombang with a sample size of 34 students. The sampling technique uses purposive sampling technique. The research results based on data analysis found that calculations using hypothesis testing, namely the t test obtained in SPSS 29, can be seen that the F is 0.149, the df is 32, the t-test result is 10.298 and the significance is 0.001. From the research results of hypothesis testing (t-test), significant results were obtained, 0.001 > 0.05. The t-test calculation result of 10.298 can be seen from the value of t_(count) > t_table, namely 10.298 > 2.036. So it can be concluded that Ho is rejected and Ha is accepted, meaning that there is a significant influence between the provision of ICT (Information and Communication Technology) based learning media on interest in studying science and science class IV at SDN 156 Maga Lombang